FOXOs: masters of the equilibrium. (15th October 2021) - Gui, Tianshu; Burgering, Boudewijn M. T.
Abstract : Forkhead box O (FOXO) transcription factors (TFs) are a subclass of the larger family of forkhead TFs. Mammalians express four members FOXO1, FOXO3, FOXO4, and FOXO6. The interest in FOXO function stems mostly from their observed role in determining lifespan, where in model organisms, increased FOXO activity results in extended lifespan. FOXOs act as downstream of several signaling pathway and are extensively regulated through post‐translational modifications. The transcriptional program activated by FOXOs in various cell types, organisms, and under various conditions has been described and has shed some light on what the critical transcriptional targets are in mediating FOXO function. At the cellular level, these studies have revealed a role for FOXOs in cell metabolism, cellular redox, cell proliferation, DNA repair, autophagy, and many more. The general picture that emerges hereof is that FOXOs act to preserve equilibrium, and they are important for cellular homeostasis. Here, we will first briefly summarize the general knowledge of FOXO regulation and possible functions. We will use genomic stability to illustrate how FOXOs ensure homeostasis. Genomic stability is critical for maintaining genetic integrity, and therefore preventing disease. However, genomic mutations need to occur during lifetime to enable evolution, yet their accumulation is believed to be causative to aging. Therefore, the role of FOXO in genomic stability may underlie its role in lifespan and aging. Finally, we will come up with questions on some of the unknowns in FOXO function, the answer(s) to which we believe will further our understanding of FOXO function and ultimately may help to understand lifespan and its consequences. Abstract : Changes in the extracellular and intracellular environment cause 'cellular stress' that is potentially detrimental and can force an equilibrium shift from healthy to diseased and eventually organismal death. Forkhead box O (FOXO) transcription factors are regulators of the equilibrium and ensure optimal cellular function and lifespan. There are four FOXO isoforms, and hence, the question addressed here: Do FOXOs act to preserve the equilibrium as a family or in an isoform‐specific manner?